Las categorías idiomáticas del español - Campos Carrasco, Nuria (Verbum – Analecta Neolatina, 2006)
The definition of noun, adjective, verb and adverb currently does not find a general agreement in the scope of Hispanic linguistics. There have been many definitions with various different criteria. Thus, morphological, lexical, syntactic and even logical arguments have been used. Such diversity in the use of criteria is translated in an accumulation of definitions that vary from author to author and which results in the cataloguing of noun, adjective, verb and adverb representatives based on currents or on individual authors. Since, as it seems to be generally recognised, examples of each of the groups exist in more than one language it seems advisable to try to establish definitions that leave apart the particularities of each language and gather the essence of the noun, adjective, verb and adverb beings. The location of representatives of each of these categories and the description of the schemes in which they materialized will correspond to the scope of each language (that is, the determination of the idiomatic categories in each language). We present here a classification of these idiomatic categories applied to Spanish.